The development of the international initiative on the humanitarian impact of nuclear weapons and its effect on the nuclear weapons debate. (16th February 2016) - Kmentt, Alexander
Abstract: This article describes the genesis of the humanitarian initiative and the political context in which it has developed in the course of the joint cross-regional statements and the three international conferences on this issue in Norway, Mexico and Austria. It examines the key substantive conclusions that have emerged as a result of this debate and assesses their relevance for the global nuclear disarmament and non-proliferation regime. It concludes that these facts and findings warrant an urgent reassessment of the so-called security value of nuclear weapons and a nuclear deterrence-based notion of stability and security.